Effect of Fat Sources and Emulsifier Supplementation in Broiler Starter, Grower and Finisher Diets on Performance, Nutrient Digestibility, and Carcass Parameters - Kamran,J (2020)
ABSTRACT The purpose of this study was to evaluate the effect of fat sources and emulsifier supplementation in different phases on growth performance of broilers. Treatments were; (T1) basal ration (BR) which contained soy oil (SO) and had inclusion of emulsifier for whole life, (T2) BR which contained poultry fat (PO) and had inclusion of emulsifier for whole life, (T3) BR which contained oxidized oil (OO) and had inclusion of emulsifier for whole life, (T4) BR which contained SO and had inclusion of emulsifier during starter phase (T5) BR which contained PO and had inclusion of emulsifier during the starter phase, (T6) BR which contained OO and had inclusion of emulsifier during the starter phase, (T7) BR which contained SO and had inclusion of emulsifier during the starter phase (T8) BR which contained PO and had inclusion of emulsifier during the grower phase, (T9) BR which contained OO and had inclusion of emulsifier during the grower phase, (T10) BR which contained SO and had inclusion of emulsifier during the finisher phase, (T11) BR which contained PO and had inclusion of emulsifier during the finisher phase (T12) BR which contained OO and had inclusion of emulsifier during the finisher phase. The Basal ration which contained SO and supplemented emulsifier during the grower phase and throughout life increased the body weight gain. The supplementation of emulsifier in the finisher phase and throughout life in a diet which contained SO had better feed conversion ratio. The supplementation of emulsifier in the finisher phase and throughout life in SO based diet increased the dry matter and crude fat digestibility. We recommend emulsifier supplementation in the finisher phase for the economic point of view.